2018
DOI: 10.33546/bnj.395
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kelakai (Stechnolaena Palustris) Consumptions on Hemoglobin Levels Among Midwifery Students

Abstract: Background: It is estimated that 49.2% of Indonesian adolescents (10-19 years) have iron deficiency of anemia. Green vegetables can be used as an alternative consumption to meet the body's need for iron. Kelakai (Stenochlaena palustris) containing 291.32 mg-100 g of Fe has been consumed by Dayak ethnic society to prevent anemia.Objective: The aim of this study was to determine the effect of Kelakai (Stenochlaena palustris) consumptions to increase hemoglobin levels among late adolescents (17-19 years).Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…This showed that there was an increase in hemoglobin levels in female adolescents by 1.8 g/dl after being given miding fern syrup. Research conducted by Petricka (2018) on late adolescents (17-19 years old) who experienced anemia, showed that there was an increase in hemoglobin levels with anemia of 3.24 g/dl after consuming miding fern (Stenochlaena palustris) for a week. Mahyuni (2015), in her research stated that in the 2nd trimester pregnant women group after being given the miding fern (Stenochlaena palustris), there was an increase of 0.14 g/dl, while in the 2nd trimester pregnant women group after giving only iron tablets, it increased 0.49 g/dl.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that there was an increase in hemoglobin levels in female adolescents by 1.8 g/dl after being given miding fern syrup. Research conducted by Petricka (2018) on late adolescents (17-19 years old) who experienced anemia, showed that there was an increase in hemoglobin levels with anemia of 3.24 g/dl after consuming miding fern (Stenochlaena palustris) for a week. Mahyuni (2015), in her research stated that in the 2nd trimester pregnant women group after being given the miding fern (Stenochlaena palustris), there was an increase of 0.14 g/dl, while in the 2nd trimester pregnant women group after giving only iron tablets, it increased 0.49 g/dl.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini mungkin disebabkan nilai gizi pakis miding yang banyak mengandung zat besi (Fe), sehingga mengkonsumsi pakis miding diharapkan dapat mengatasi masalah anemia pada remaja putri, ibu hamil, dan ibu menyusui pada masyarakat Kabupaten Sintang. Penelitian dilakukan oleh Petricka (2018) tentang pengaruh konsumsi kelakai (Stechnolaena palustris) dalam meningkatkan hemoglobin pada mahasiswa kebidanan.…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini sejalan dengan penelitian yang dilakukan Petricka (2018) Kadar Hb yang rendah di masa kehamilan dapat menyebabkan berat badan lahir rendah, kelahiran prematur, dan kematian ibu saat persalinan. Hb rendah pada wanita hamil dapat merugikan pertumbuhan janin dan kehamilan, penting untuk memastikan kadar hemoglobin normal ibu hamil agar menghindari dari risiko yang berbahaya.…”
Section: Pengaruh Pemberian Pakis Miding (Stenochlaena Palustris) Ter...unclassified
“…Kemudian senyawa Fe pada kalakai dapat meningkatkan kadar hemoglobin. Hal ini dibuktikan dengan meningkatnya kadar hemoglobin yang signifikan (3,24 g/dl) setelah mengonsumsi kalakai selama seminggu (p≤0,05) dengan kadar hemoglobin setelah intervensi pada kelompok kontrol lebih tinggi 0,03 g/dl dibandingkan kelompok kalakai, namun berdasarkan analisis tidak terdapat perbedaan bermakna pada kedua kelompok (p≥0,05) [16]. Studi kasus lainnya melaporkan kadar Hb siswi yang mengalami anemia meningkat sebesar 6,859 gr/dl setelah pemberian ekstrak kalakai [17].…”
Section: Antioksidan Kalakai Sebagai Penambah Hemoglobinunclassified